Effectiveness and Safety Data in Rheumatoid Arthritis Patients after Switching from Originator Rituximab to Biosimilar Rituximab (CT-P10) - Ekin, Ali; Misirci, Salim; Lermi, Nihal; Kutlu, Nagehan Dik; Coskun, Belkis Nihan; Yagız, Burcu; Dalkılıç, Ediz; Pehlivan, Yavuz (Aktuelle Rheumatologie, 2024)
Backgorund Rituximab is an anti-CD20 monoclonal antibody used in the treatment of rheumatoid arthritis. The molecule CT -P10 is a biosimilar of rituximab used in rheumatoid arthritis and has the same safety and efficacy.Material and methods The aim of our study was to investigate whether drug efficacy decreases after the mandatory switch from originator rituximab to biosimilar rituximab, whether there is an increase in disease activity indices in patients with rheumatoid arthritis receiving rituximab, that could indicate decreased efficacy, and whether the frequency of adverse events related to drug safety remains comparable. We analysed 131 patients with rheumatoid arthritis who received rituximab therapy between January 2010 and December 2022.These patients were switched from the originator rituximab to biosimilar rituximab and followed up.Results After the switch, a statistically significant decrease in HAQ, DAS-28-CRP, and CDAI scores was observed, while there was no increase in disease activity in other scales. We found that the frequency of adverse events associated with originator rituximab treatment was correlated with anti-CCP positivity (OR=5.436; p=0.006), the presence of an infection requiring hospitalisation (OR=3.917; p=0.012), and the duration of first rituximab treatment (OR=1.032; p<0.001). Similarly, adverse events associated with the use of biosimilar rituximab were associated with a history of infection requiring hospitalisation (OR=50.762; p<0.001).There was not a statistically significant difference between the originator and biosimilar rituximab for total adverse events.Conclusion Our results suggest that the use of biosimilar rituximab does not lead to an increase in disease activity indices, indicating comparable efficacy, and that the risk of adverse drug reactions is largely similar between the use of original rituximab and biosimilar rituximab.
Keywords: biosimilar; effectiveness; rheumatoid arthritis; rituximab; safety